Studnia przydrożna z XVI-XVII wieku na Ostrowie Tumskim w Poznaniu - Antowska-Gorączniak, Olga; Lech, Paweł; Sikorski, Andrzej (Ecclesia. Studia z Dziejów Wielkopolski, 2018)
In July 2008 a roadside well was discovered on the cathedral island in Poznań (to date at least five drawing wells from the late Middle Ages and modern times have been registered). The well was unearthed at the rose square (excavation pit 51/2008) about 18 m from the facade of the church of the Blessed Virgin Mary (and the now nonexistent churchyard) at the level of 56.09 meters above sea level (rubble fill-in) – 50.61 meters above sea level (end of exploration) – Fig. 1. The object was situated directly next to the road, in a large oval or quadrilateral pit (with rounded corners) ca 3.6 m in diameter, and was ca 5.5 m deep. The wooden construction which protected the walls of the object was done in the post and beam technique – Fig. 2. Many different objects fell (were thrown) into the well while water was being drawn from it, perhaps some of them were redeemed while other remained at the bottom. However, most of the “sunk” relics got into the well while it was being dug or repaired, but especially when it was filled in, i.e. when water was no longer drawn from it (Figs. 4 and 5). The well, which was sunk during the rule of Bishop Jan Lubrański (1499-1520), i.e. at a time of prosperity of Ostrów Tumski in the 16th century, was in use and water was drawn from it in the 15/16-17th centuries. It is difficult to assert what reasons decided about its being